VALUE-BASED MANAGEMENT CAPITALISM VS SOCIALISM PROBLEMS IN THE ISLAMIC ECONOMIC: VALUE-BASED MANAGEMENT CAPITALISM VS SOCIALISM PROBLEMS IN THE ISLAMIC ECONOMIC - Joki Hartono Tri Nugroho; Regas Panji Pratomo; Indrian Sasmito Adi, Handaru (Universitas Airlangga, 2024)
The problem with both economic systems, capitalism and socialism, is that they cannot achieve the desires and aspirations of the people as actors of economic policy. Both systems prioritize profit over satisfaction or people's rights. Departing from the various problems that exist in society, the author tries to examine this problem by organizing the two Islamic economic systems. The aim is to examine the problems faced by the economic systems of capitalism and socialism in dealing with economic problems and also to see how the Islamic economic system deals with economic problems. Desk research, or